Jerome Bruner's Theory of Learning to Improve Basic School Students' Understanding of Numbers by Learning in Stage - Dewi Netta Febrianti; Jayanti Putri Purwaningrum (Mathematics Education Journal, 2021)
Mathematics is a subject that is disliked by most students. This has resulted in a lot of children who are not enthusiastic about this lesson since elementary school. Elementary school is a place where children start knowing what numbers are, what numbers are and how a number looks. Numbers become the basis for children before learning about mathematics. There are so many branches in numbers that children need to know, starting from the basics of numbers, namely natural numbers, developing into whole numbers, whole numbers, and fractions. This is why the methods of learning mathematics must be well determined, at this time many learning methods have emerged with various criteria. Because of this, the writer tries to find the right theoretical solution according to the number material which has developing properties, the method that can be used is the Bruner Theory, which is to learn by understanding the basics first before proceeding with something that is more difficult because mathematics is an abstract concept.